Estudio Transversal de Procesos Administrativos en Municipios de la Huasteca Norte - González, Pablo Martínez; Hernández, Hugo Jesús Ochoa; Cortés, Mario Eduardo Ibarra (European Scientific Journal, ESJ, 2018)
This paper focuses, first, on presenting a tool designed as a methodological proposal to help the municipal administrations to improve their administrative processes. This is possible by taking into consideration the phases that integrates it (Planning, Organization, Integration, Direction and Control) in order to identify the steps of the process where there are failures. This, however, makes it possible to detect them, apply corrective measures, and ensure that they are able to carry out processes of continuous improvement. Secondly, the document presents a study in which a methodology was applied. Here, it could be documented that for the case of the municipalities of Tamasopo, Tamuín and Ciudad Valles in the State of San Luis Potosí, a lack of systematization was detected in the administrative processes. The results have allowed us to perceive a differentiated opinion between the perception that the Heads of Department have regarding the application of the Administrative Process and the opinion that operative workers have regarding the phases of planning, organization, integration, direction, and control.